The Effect of the Cooperative Integrated Reading and Composition (CIRC) Learning Model on Elementary School Students' Reading Comprehension Skills - Usman, Usman; Burhan, Imron; Rahmadani, Nurastri (Darul Yasin Al Sys, 2026)
Limited research has examined cooperative learning models that integrate reading and writing activities to improve students’ literacy competencies, although low reading comprehension skills remain a significant issue among fifth-grade students at UPTD SD Negeri 28 Parepare, where conventional learning methods have commonly been used. This study aims to describe students’ reading comprehension skills taught with and without the Cooperative Integrated Reading and Composition (CIRC) model and to analyze the effect of the CIRC model on fifth-grade students’ reading comprehension skills at UPTD SD Negeri 28 Parepare. A quantitative approach with a quasi-experimental design using a balanced control group was employed, with samples selected through a random grouping technique. Data were collected using pretests and posttests. The data were analyzed through descriptive and inferential statistics, including normality tests, homogeneity tests, N-Gain analysis, and an independent samples t-test. The findings indicate a significant difference in reading comprehension skills between the experimental and control groups, with the experimental group achieving a higher average score. The independent samples t-test further supported this result, showing a significance value (Sig. 2-tailed) below 0.05, which indicates that the CIRC learning model had a significant effect on students’ reading comprehension skills. The study concludes that integrating reading and writing activities through heterogeneous group interaction effectively improves students’ reading comprehension compared to conventional learning methods. These findings contribute to the development of cooperative learning strategies and extend the literature on integrated literacy instruction at the elementary school level. The study also provides practical implications for educators to adopt collaborative and activity-based learning models such as CIRC to create more meaningful literacy learning experiences, while further research is recommended to examine the application of this model across different educational levels.